Mongolia : Technical Assistance Report-High Frequency Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2022)
The IMF conducted a remote technical assistance (TA) mission from March 1 to 12, 2021, to help the National Statistics Office of Mongolia (NSOM) compile a monthly indicator of economic activity (MIEA). Experimental results describe monthly economic activity from January 2010 to January 2021 as well as the impact of the COVID-19. This second mission for developing the MIEA was funded by the IMF's Data for Decisions trust fund1 (D4D).